Sleep disorders and suicide attempts following discharge from residential treatment - Bishop, Todd M.; Youngren, Westley A.; Klein, John S.; Speed, Katrina J.; Pigeon, Wilfred R. (Frontiers in Sleep, 2023)
Introduction: Suicide is a significant public health concern and its prevention remains a top clinical priority of the Veterans Health Administration. Periods of transition in care (e.g., moving from inpatient to outpatient care) represent a period of increased risk. Sleep disorders are prevalent amongst Veterans and are modifiable risk factor for suicide. The present study examined the relationship of sleep disorders to time to suicide attempt amongst Veterans known to have attempted suicide in the 180 days following discharge from a Mental Health Residential Rehabilitation Treatment Program.